2017
DOI: 10.1111/ajgw.12297
|View full text |Cite
|
Sign up to set email alerts
|

Modelling consumers' heterogeneous preferences: a case study with Chilean wine consumers

Abstract: Background and Aims: Understanding consumers' preferences is key to making a successful product, but preferences are heterogeneous. We compare three approaches to consider preference heterogeneity in discrete choice models: (i) systematic preference variations based on socio-demographic characteristics; (ii) latent classes; and (iii) hybrid choice models with latent variables measuring consumers' attitudes. Methods and Results: Data from a stated choice survey of Chilean wine consumers were analysed using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Therefore, the greater the brand awareness, the more renowned brands of alcoholic beverages are bought. In other words, shoppers of alcoholic beverages prefer good brands (Palma et al, 2017).…”
Section: Results Obtained In the Hypothesis Contrastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the greater the brand awareness, the more renowned brands of alcoholic beverages are bought. In other words, shoppers of alcoholic beverages prefer good brands (Palma et al, 2017).…”
Section: Results Obtained In the Hypothesis Contrastingmentioning
confidence: 99%
“…In this regard, an impulsive decision-making style leads the individual to buy more alcohol without having to worry about the price or whether it is really needed or not, and simply buy it without any previous planning. In contrast, a decision-making style confused by information overload implies a blocked buyer decision owing to excessive alternative options, meaning that they tend to buy fewer beverages and choose the most well-known and those in which they have greater confidence (Palma et al, 2017). This leads us to formulate the following hypothesis:…”
Section: Buying Alcoholic Beverages: Individual Factorsmentioning
confidence: 99%
“…Pomarici et al (2017) sorted the variables into four groups: socio–demographics; psychographics, especially involvement and knowledge; lifestyle; and behaviour, such as frequency of consumption and consumption occasion. They, along with Arnould et al (2002, cited in Palma et al , 2014) also named four variables that can account for market segmentation: geographic, demographic, behavioural and psychographic. Bruwer et al (2002) pointed out that demographic characteristics alone are less useful to form segments regarding wine, as “wine consumers can be demographically similar but significantly different in terms of attitudes, consumption behaviour, lifestyle” (Bruwer et al , 2002: 221).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Palma et al (2014) found that most of the applied wine market segmentation techniques rely on a psychometric approach. Hall and Winchester (1999) based their research on beliefs, attitudes, values and product preferences when purchasing wine.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation